Information technology of the anticipatory control of realization of actions on emergency situations prevention - Mukhin, Владимир Иванович; Samoylov, Станислав Викторович (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The information technology of the anticipatory control on prevention of emergency situations is submitted. Verbal and information models of the anticipatory control are considered, and also the basic stages of the methodical apparatus of realization of actions on prevention of emergency situations are submitted.